Portomesenteric Thrombosis Secondary to Acute Cholecystitis: A Case Report - Haseeb Ahmad Chaudhary; Ibrahim Yusuf Abubeker; Kamran Mushtaq; Khaldun Obeidat; Anand Kartha (Case Reports in Gastrointestinal Medicine)
Portomesenteric venous thrombosis (PMVT) is an uncommon clinical problem. Common risk factors include intra-abdominal infections, abdominal surgeries, malignancy, cirrhosis, and inherited thrombophilia. Early recognition and treatment of PMVT are important to avoid serious complications like mesenteric ischemia and infarction. Acute cholecystitis is a clinical condition encountered daily but rarely may be complicated by development of portomesenteric venous thrombosis. Only few cases have been reported of superior mesenteric vein thrombosis secondary to cholecystitis. We report a case of a forty-one-year-old male patient who developed partial portal and superior mesenteric vein thrombosis after mild acute cholecystitis for which surgery had been deferred. Patient had no other identifiable risk factors for thrombosis. Patient was successfully treated with 6 months of anticoagulation with warfarin and complete recanalization of portomesenteric veins was achieved at the end of treatment.